Water, sanitation and agriculture linkages with health and nutrition improvement - Nicolas Gerber; Joachim von Braun; Muhammed Abdella Usman; Mohammad Monirul Hasan; Charles Yaw Okyere; Ruchi Vangani; Doris Wiesmann (University of Bonn, Center for Development Research (ZEF), 2019)
In 2010, the United Nations General Assembly recognized access to safe water and sanitation infrastructure a matter of human right. This right is reflected in Sustainable Development Goal 6, whose targets 1 and 2 point to universal access to safe and affordable drinking water and adequate sanitation by 2030, in a gender equitable way. Progress towards these targets has been recorded, building on successes achieved under the previous framework of the Millennium Development Goals (Target 7.c). These positive developments could be expected to spill over to other dimensions of human development, health and nutrition in particular. Yet, progress in either of these dimensions, particularly among young children (SDG target 2.2 on ending all forms of malnutrition), is not commensurate. In this paper, we advocate for a systemic approach to water management for improved health and nutrition. We focus on rural and peri-urban areas of the developing world, where multi-purpose water systems are particularly relevant. As competition for safe water resources intensifies, it is important to understand the trade-offs between specific uses and their implications for health and nutrition, based on the gender and age of individuals. We conduct statistical and econometric analyses of secondary, nationally representative data for four countries: Bangladesh, Ethiopia, Ghana and India. These data sets have been routinely used to report on progress toward SDG 6 (availability and sustainable management of water and sanitation for all) and SDG 2 (ending hunger and achieving food security and improved nutrition for all). Our cross-sectional analysis reflects the positive association between access to improved sanitation infrastructure and long-term child nutrition outcomes (height-for-age and weight-for-age). On the other hand, the analysis fails to demonstrate a positive association between access to improved drinking water sources and the same child nutrition indicators. In the next step, we investigate the associations between multi-use water systems, especially around agricultural activities, and health and nutrition. To that end, we compile data from four household surveys we collected in the same countries, including indicators on the type of irrigation system. The regression analysis of this pooled dataset is complemented by an in-depth, context-specific analysis of behavior around drinking water use and irrigation practices. The analyses reveal a low correlation between water quality at the point of source and water quality at the point of use, drawing attention to behavioral issues around water use. Similarly, the prevalence of open defecation seems much more important to health and nutrition than the existence of sanitation infrastructure. Finally, irrigation is not per se a detrimental factor for drinking water quality or nutrition, but the integration of waste water irrigation in particular needs to be carefully managed in order to avoid adverse nutrition and health effects.
Keywords: Q15; Q01; Q19; I12; 330; multi-purpose water system; sanitation; agriculture; behavior; knowledge; nutrition